THE DIPLOMACY OF QUALIFYING INDUSTRIAL ZONES - SHOUGARIAN, Rouben (CENTRAL ASIA AND THE CAUCASUS, 2015)
The author investigates an alternative, indirect settlement between Armenia and Turkey expected to lead the negotiations out of the dead end into which they were pushed by the refusal of Ankara and Yerevan to ratify the Zürich Protocols. On the one hand, American-Swiss mediation and the shuttle diplomacy of 2008-2009, crowned by the sensational signing of the Turkish-Armenian protocols, inflated international expectations. On the other, the euphoria created by what looked like a fundamental solution to one of the most complicated conflicts of the twentieth century proved to be short-lived.In the rapidly changing geopolitical situation around the Southern Caucasus, the opening of the Turkish-Armenian border has acquired a new meaning in the context of regional and global security. This problem calls not for mind-boggling initiatives inevitably doomed to loud diplomatic failures (this is what happened to the signed and not ratified protocols), but for less ambitious, albeit implementable programs.1 We must study and apply the successful experience of trade and economic programs elaborated for border regions of geographical neighbors divided by political conflicts.This article offers for discussion the Qualifying Industrial Zones (QIZ) project the Clinton Administration proposed in 1996 to Israel, Palestine, Egypt, and Jordan to be applied within the framework of normalizing Armenian-Turkish relations. The author contemplates the possibility of limited opening of the Armenian-Turkish border as a natural and necessary result of QIZ in the Kars-Gyumri border region and looks further into the political feasibility of setting up two more QIZs. One of them can be set up at the border between Armenia and the Nakhchivan Autonomous Republic (an exclave of Azerbaijan), the other, at the meeting point of the borders of Georgia, Armenia and Azerbaijan. In both cases this might prove to positively affect the Nagorno-Karabakh conflict and intensify integration in the Black Sea region and the Southern Caucasus. At the same time, these developments might contain Baku’s negative response to the opening of the Armenian-Turkish border. An Armenian-Turkish QIZ set up with the U.S. brokerage might become a serious stabilizing factor against the background of new challenges to regional and global security and the deepening dividing lines in the Southern Caucasus and around it.